High-latitude Observations of Dissipation-range Turbulence by the Ulysses Spacecraft during the Solar Minimum of 1993–96: The Spectral Break and Anisotropy - Abigale S. Watson; Charles W. Smith; Anastasia V. Marchuk; Matthew R. Argall; Colin J. Joyce; Philip A. Isenberg; Bernard J. Vasquez; Nathan A. Schwadron; Neil Murphy (The Astrophysical Journal, 2024)
We examine Ulysses magnetic field observations from 1993 to 1996 as the spacecraft made its first fast-latitude scan from the southern to the northern hemisphere. Most of the observations we use are representative of high-latitude solar minimum conditions. We examine magnetic field power spectra characteristics of interplanetary turbulence at high frequencies, where the spectrum breaks from an inertial range into the ion dissipation range. The onset and spectral index of the dissipation spectrum are consistent with low-latitude observations at 1 au. Both ranges have a ratio of power in perpendicular magnetic field components to parallel components near 3. The power spectrum ratio test developed by Bieber et al. for single-spacecraft analyses that determines the underlying anisotropy of the wave vectors yields only marginally more energy associated with field-aligned wave vectors than perpendicular wave vectors when comparing the inertial and dissipation-range spectra. The lack of significant change in the anisotropies between the inertial and dissipation ranges contrasts strongly with the turbulence found typically for 1 au near-ecliptic observations, where significant differences in both anisotropies are observed.